stiff1 - k1(1,1)=l*l k1(1,2)=l*m k1(2,1)=l*m k1(2,2)=m*m...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Sheet1 Page 1 %stiff1.m function [k]=stiff1(L,ll,aa) k1=zeros(2) l=ll(1) m=ll(2) A=aa(1) E=aa(2)
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: k1(1,1)=l*l k1(1,2)=l*m k1(2,1)=l*m k1(2,2)=m*m k=[k1,-k1-k1,k1] k=(A*E/L)*k...
View Full Document

This note was uploaded on 06/07/2011 for the course EML 4507 taught by Professor Kim during the Fall '11 term at University of Florida.

Ask a homework question - tutors are online